Pengaruh Pendekatan STEAM Terhadap Kemampuan Berpikir Kritis Anak Kelompok B Di TK An-Nur Palembang - Nurhaliza, Anisa; Lidia Oktamarina; Elsa Cindrya; Leny Marlina (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
STEAM as an approach is a means for students to create science and technology-based ideas/concepts through thinking and exploring activities in solving problems based on five integrated disciplines. Critical thinking skills are important to be honed from an early age, because they can help in expanding children's knowledge. This study aims to determine the effect of the STEAM (Science, Technology, Engineering, Art, and Mathematics) approach on the critical thinking skills of group B children at An-Nur Kindergarten in Palembang City. The research method used is quantitative with a Pre-Experimental design in the form of One Group Pretest-Posttest Design. The research sample consisted of 16 class B2 children selected through purposive sampling techniques. Data collection techniques used observation, tests, and documentation, then analyzed with a t-test. The results of the study showed an increase in children's critical thinking skills after being given treatment through the STEAM approach. This is evidenced by the difference in the average pretest score (57.75) and posttest (86.5). The hypothesis test yielded a t-test of 10.37, which is greater than the t-table of 2.131 at a 5% significance level. Therefore, Ha is accepted and Ho is rejected. Therefore, it can be concluded that the STEAM approach has a significant effect on the critical thinking skills of 5–6-year-old children at An-Nur Kindergarten in Palembang.